Yin Yang and organizational performance : five elements for improvement and success - Law, Kris M.Y; Kesti, Marko (Springer London, 2014)
Presenting an innovative approach to the field of organizational management, this book proposes a Yin Yang (cosmological) perspective as an alternative to existing management concepts, serving to conceptualize the organization processes in a more holistic way. Maximizing reader insights into the concept of Yin Yang and how it can be applied to the areas of human resource based performance development and management, 'Yin Yang and Organizational Performance' includes case studies that illustrate ways to properly utilize human resource innovativeness and emotional intelligence. Encompassing engineering and humanist perspectives, this books shares tips and insights designed to provide management and business leaders with new ways of understanding and organizing human capital.